Preparation method of high-entropy composite oxygen carrier for chemical looping gasification hydrogen production

Through low-temperature ultrasonic assisted mixing, electrochemical activation and low-temperature calcination processes, high entropy composite oxygen carriers are prepared, which solves the problems of sintering and high energy consumption caused by traditional high-temperature calcination methods, and achieves efficient and stable oxygen release and catalytic activity. It is suitable for chemical chain gasification and hydrogen production.

CN119912977AActive Publication Date: 2025-05-02SOUTH CHINA AGRICULTURAL UNIVERSITY +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510277534.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2025-05-02
Estimated Expiration
2045-03-10

AI Technical Summary

Technical Problem

The existing high entropy oxygen-carrying method relies on high-temperature calcination, which leads to the loss of sintering and catalytic activity of the oxygen-carrying body, and has high energy consumption, making it impossible to maintain stability and catalytic activity in a complex atmosphere for a long time.

Method used

High entropy composite oxygen carrier is prepared by combining low-temperature ultrasonic assisted mixing, electrochemical activation and low-temperature calcining processes. This method avoids sintering problems and reduces energy consumption through low-temperature freeze-drying, electrochemical activation and low-temperature calcination.

Benefits of technology

It significantly improves oxygen release capacity, stability and catalytic activity, is suitable for clean energy technology fields such as hydrogen production such as chemical chain gasification, and has significant industrial application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912977A_ABST
    Figure CN119912977A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a high-entropy composite oxygen carrier for chemical looping gasification hydrogen production. According to the method, the high-entropy composite oxygen carrier with excellent oxygen release performance and high stability is prepared by combining low-temperature ultrasonic-assisted mixing, electrochemical activation and a low-temperature calcination process. The preparation method comprises the following specific steps: dissolving nitrates of Fe, Co, Ni, Cu and Mn in deionized water according to a molar ratio of 1: 1: 1: 1: 1: 1, and adding sodium chloride (NaCl) and polyvinylpyrrolidone (PVP) to adjust the property of the solution so as to form uniform sol; performing low-temperature freeze drying to obtain anhydrous gel powder; then carrying out electrochemical activation and compounding with graphene; and finally, calcining at a low temperature of 300-500 DEG C, washing and drying to obtain the high-entropy composite oxygen carrier. The oxygen carrier has a high specific surface area (gt; according to the present invention, the prepared catalyst has characteristics of uniform particle size distribution (50 m < 2 > / g), excellent pore size distribution (2-50 nm), good crystal structure (cubic system) and more than 100 times of oxidation reduction cycle stability, the oxygen transmission rate is increased by 50%, the sintering resistance is enhanced by more than 40%, the oxygen release performance and the catalytic activity are significantly improved, the sintering problem caused by the traditional high temperature calcination is avoided, the energy consumption is reduced, and the preparation method is simple. The method is suitable for an efficient and stable chemical-looping gasification hydrogen production process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing a high-entropy composite oxygen carrier, and in particular to the preparation of a high-entropy oxygen carrier used in chemical chain gasification hydrogen production. The present invention is widely applicable to chemical chain gasification hydrogen production, chemical chain reforming and other clean energy technology fields, and has significant industrial application value. Background Art

[0002] With the increase in global energy demand and the focus on sustainable energy solutions, the potential of hydrogen as a clean energy source has been increasingly valued. In the field of hydrogen preparation, chemical chain gasification hydrogen production technology has become one of the research hotspots due to its high efficiency and low energy consumption. In this technology, oxygen carriers are key materials responsible for providing oxygen to promote gasification reactions. Although traditional high-entropy oxygen carriers show good performance in catalysis and oxygen release, existing preparation methods often rely on high-temperature calcination, which can easily lead to sintering of oxygen carriers and loss of catalytic activity under high temperature conditions, and have high energy consumption.

[0003] At present, some studies have proposed different methods for preparing high-entropy oxygen carriers. For example, patent CN 118988338A (a high-entropy oxide and its preparation method and application) uses a combination of PVP template method and freeze-drying technology to prepare a high-entropy oxide with good catalytic activity. Another patent CN 116654993 A (a high-entropy oxide oxygen carrier and its preparation method and application) uses a citric acid sol-gel method combined with a mixed solution of polyethylene glycol and water to prepare a high-entropy oxide with good oxygen release performance. In addition, patent CN 117019168 A (a high-stability transition metal high-entropy oxygen carrier and its preparation method and application) combines different transition metals with non-transition metals to propose a high-entropy oxygen carrier with high stability, and applies it in chemical chain gasification.

[0004] Although the above technologies have made some progress in improving the catalytic performance and stability of high entropy oxygen carriers, they still face the following challenges:

[0005] (1) Existing methods for preparing high entropy oxygen carriers often rely on high-temperature calcination, which can lead to sintering and loss of activity of the oxygen carrier;

[0006] (2) Existing preparation methods are usually energy inefficient and have high energy consumption;

[0007] (3) Most methods are unable to maintain the stability and catalytic activity of oxygen carriers in complex atmospheres for a long time.

[0008] Therefore, the present invention proposes an innovative method for preparing a high-entropy composite oxygen carrier, which can significantly improve the oxygen release capacity, stability and catalytic activity through the combination of low-temperature ultrasonic-assisted mixing, electrochemical activation and low-temperature calcination process, while avoiding the sintering problem in traditional methods, reducing energy consumption, and meeting the demand for efficient and stable oxygen carriers in chemical chain gasification hydrogen production. Summary of the invention

[0009] To achieve the above object, the present invention provides a method for preparing a high entropy composite oxygen carrier (FeCoNiCuMnOx high entropy oxygen carrier), comprising the following steps:

[0010] S1: Preparation and mixing of metal salt solution;

[0011] S2: adding electrolyte and gelling agent to the metal salt solution to form a stable metal complex sol;

[0012] S3: freeze-drying the sol at low temperature to obtain anhydrous gel powder;

[0013] S4: electrochemically activating and compounding the freeze-dried powder;

[0014] S5: After the composite material is calcined at low temperature, post-processing steps such as screening and washing are performed to obtain a high entropy composite oxygen carrier.

[0015] The metal salt dissolving elements described in step S1 are iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), and manganese (Mn) selected as main metal elements, and the preferred molar ratio is Fe:Co:Ni:Cu:Mn=1:1:1:1:1.

[0016] Furthermore, at room temperature (about 25°C), the above-mentioned metal nitrates (Fe(NO3)3·9H2O, Co(NO3)2·6H2O, Ni(NO3)2·6H2O, Cu(NO3)2·5H2O, Mn(NO3)2·4H2O) are weighed according to the above-mentioned proportions, added one by one into deionized water, and stirred at 300 rpm using a magnetic stirrer until all the metal salts are completely dissolved to form a uniform solution, thereby preparing a metal salt mixed solution with a concentration of 0.1 mol / L.

[0017] The ultrasonic wave described in step S1 is produced by using an ultrasonic cleaner with a power of 500W and a frequency of 20kHz.

[0018] Furthermore, the metal salt solution was placed in an ultrasonic cleaner and subjected to ultrasonic treatment for 30 minutes with intermittent operation (5 minutes of ultrasonic treatment each time and 2 minutes of rest) to prevent overheating.

[0019] The electrolyte in step S2 is a sodium chloride (NaCl) solution.

[0020] Further, sodium chloride (NaCl) is added to the metal salt solution prepared in step S1, and the mixture is continuously stirred at room temperature until the sodium chloride is completely dissolved and the concentration reaches 0.05 mol / L.

[0021] The gelling agent in step S2 is polyvinyl pyrrolidone (PVP).

[0022] Furthermore, PVP is dissolved in a small amount of deionized water to prepare a PVP solution with a concentration of 0.5%-2%, which is slowly added to the metal salt solution prepared in step S1 and stirred for 30 minutes until a uniform sol is formed.

[0023] The freeze drying in step S3 is performed using a freeze dryer.

[0024] Furthermore, the sol prepared in step S2 is placed in a refrigerator at -10 to -30°C for pre-cooling for 2 hours until the surface begins to freeze.

[0025] Further, the pre-cooled sol was transferred to a freeze dryer, and the temperature was set at -40 to -60°C, the pressure was 0.05 mbar to 0.1 mbar, and the drying time was 24 hours until an anhydrous gel was obtained.

[0026] The electrochemical electrolyte solution described in step S4 is a 0.1 mol / L sodium sulfate (Na2SO4) solution.

[0027] Furthermore, the freeze-dried powder material and a platinum electrode were placed in an electrochemical cell, and an Ag / AgCl electrode was used as a reference electrode.

[0028] The electrochemical activation parameters of step S4 are: at room temperature, applying a voltage of 1-3 V, the activation time can be set to 1 h-3 h, and performing cyclic voltammetry scanning at a scanning rate of 5 mV / s.

[0029] The composite material described in step S4 uses a mass ratio of oxygen carrier: graphene = 1:0.05-0.1.

[0030] Furthermore, under the above electrochemical activation conditions, electrochemical deposition was performed for 1 hour to ensure good recombination of graphene and the oxygen carrier.

[0031] The low-temperature calcination in step S5 is carried out in a Maffei furnace.

[0032] The calcination atmosphere in step S5 can be carried out in air, nitrogen or hydrogen.

[0033] Furthermore, in step S5, the calcination temperature is 300-450° C., the calcination time is 3-6 h, and the heating rate is 1-4° C. / min.

[0034] Furthermore, the calcined material is washed with deionized water until the pH value of the washing solution is close to neutral.

[0035] Furthermore, the washed material is dried at 60° C. for 12 hours until constant weight is reached to obtain the final high entropy composite oxygen carrier.

[0036] The high entropy composite oxygen carrier prepared by the above steps has the following significant advantages:

[0037] (1) High oxygen release capacity: The combination of low-temperature ultrasonic-assisted mixing and electrochemical activation technology can significantly improve the oxygen release rate and efficiency of the oxygen carrier in a high-temperature environment.

[0038] (2) Excellent catalytic performance: The introduction of composite materials improves the catalytic activity and selectivity of oxygen carriers, making them suitable for chemical chain gasification hydrogen production and other catalytic reactions.

[0039] (3) High stability and cycle performance: The low-temperature calcination process avoids the sintering problem in the traditional high-temperature calcination process, and the oxygen carrier maintains high stability and cycle performance during long-term reactions.

[0040] (4) Energy saving and environmental protection: This method reduces energy consumption through low-temperature synthesis and electrochemical activation process, avoiding the pollution generated by traditional high-temperature calcination process. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 Flow chart of preparation of high entropy composite oxygen carrier for hydrogen production by chemical chain gasification DETAILED DESCRIPTION

[0042] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0043] Example 1 Preparation of high entropy composite oxygen carrier FeCoNiCuMn-500℃

[0044] (1) Preparation and mixing of metal salt solution: Metal nitrates were weighed at a molar ratio of Fe:Co:Ni:Cu:Mn=1:1:1:1:1 and dissolved in deionized water to prepare a mixed solution with a concentration of 0.1 mol / L.

[0045] (2) Adding electrolytes and gelling agents: Add 0.05 mol / L NaCl solution and 1% PVP solution by mass to the above solution and stir for 30 minutes to form a uniform sol.

[0046] (3) Low-temperature freeze drying: The sol was precooled to -20 °C and then freeze-dried at -50 °C and 0.1 mbar for 24 h to obtain anhydrous gel powder.

[0047] (4) Electrochemical activation and recombination: The freeze-dried powder and platinum electrode were placed in a 0.1 mol / L Na2SO4 solution, and a voltage of 1.5 V was applied for activation for 2 hours. Then, graphene was added at a mass ratio of 1:0.05, and electrochemical deposition was continued for 1 hour to complete the recombination process.

[0048] (5) Low-temperature calcination and post-treatment: The composite material was placed in a muffle furnace, heated to 500°C at a heating rate of 2°C / min, maintained for 4 hours, and naturally cooled to room temperature. After being taken out, it was washed with deionized water until the pH of the washing liquid was close to neutral, and dried at 60°C for 12 hours to obtain a FeCoNiCuMnOx high entropy composite oxygen carrier, recorded as FeCoNiCuMn-500°C.

[0049] The high entropy composite oxygen carrier prepared in the above steps has been tested to have a specific surface area of ​​60m 2 / g, the pore size distribution is between 2-50nm, the crystal structure is cubic, the oxygen transmission rate is increased by 50%, the sintering resistance is enhanced by more than 40%, the redox cycle stability is more than 100 times, and the oxygen release performance and catalytic activity are significantly improved.

[0050] Using pine wood powder as raw material, chemical chain gasification hydrogen production test was carried out at 800°C, the reduction time was 35min, the synthesis gas yield was 0.98Nm3 / h, the synthesis gas selectivity was 75%, the hydrogen production purity was 99.1%, and after 100 cycles, the performance decayed by 3.1%, showing good reaction characteristics.

[0051] Example 2 Preparation of high entropy composite oxygen carrier FeCoNiCuMn-450℃

[0052] (1) Preparation and mixing of metal salt solution: Metal nitrates were weighed at a molar ratio of Fe:Co:Ni:Cu:Mn=1:1:1:1:1 and dissolved in deionized water to prepare a mixed solution with a concentration of 0.1 mol / L.

[0053] (2) Add electrolytes and gelling agents: Add 0.05 mol / L NaCl solution and mass

[0054] The PVP solution with a molar fraction of 1.5% was stirred for 30 minutes to form a uniform sol.

[0055] (3) Low-temperature freeze drying: The sol was precooled to -15 °C and then freeze-dried at -45 °C and 0.08 mbar for 24 h to obtain anhydrous gel powder.

[0056] (4) Electrochemical activation and recombination: The freeze-dried powder and platinum electrode were placed in a 0.1 mol / L Na2SO4 solution, and a voltage of 1.2 V was applied for activation for 2 hours. Then, graphene was added at a mass ratio of 1:0.07, and electrochemical deposition was continued for 1 hour to complete the recombination process.

[0057] (5) Low-temperature calcination and post-treatment: The composite material was placed in a muffle furnace, heated to 450°C at a heating rate of 2°C / min, maintained for 3 hours, and naturally cooled to room temperature. After being taken out, it was washed with deionized water until the pH of the washing liquid was close to neutral, and dried at 60°C for 12 hours to obtain a high-entropy composite oxygen carrier, which was recorded as FeCoNiCuMn-450°C.

[0058] The high entropy composite oxygen carrier prepared in the above steps has been tested to have a specific surface area of ​​58 m 2 / g, the pore size distribution is between 3-45nm, the crystal structure is cubic, the oxygen transmission rate is increased by 48%, the sintering resistance is enhanced by more than 38%, and the redox cycle stability exceeds 100 times.

[0059] Using pine wood powder as raw material, chemical chain gasification hydrogen production test was carried out at 800°C, the reduction time was 35min, the synthesis gas yield was 0.97Nm3 / h, the synthesis gas selectivity was 77%, the hydrogen production purity was 99.2%, and after 100 cycles, the performance decayed by 3.3%, showing good reaction characteristics.

[0060] Example 3 Preparation of high entropy composite oxygen carrier FeCoNiCuMn-400℃

[0061] (1) Preparation and mixing of metal salt solution: Metal nitrates were weighed at a molar ratio of Fe:Co:Ni:Cu:Mn=1:1:1:1:1 and dissolved in deionized water to prepare a mixed solution with a concentration of 0.1 mol / L.

[0062] (2) Adding electrolytes and gelling agents: Add 0.05 mol / L NaCl solution and 2% PVP solution by mass to the above solution and stir for 30 minutes to form a uniform sol.

[0063] (3) Low-temperature freeze drying: The sol was precooled to -25 °C and then freeze-dried at -55 °C and 0.1 mbar for 24 h to obtain anhydrous gel powder.

[0064] (4) Electrochemical activation and recombination: The freeze-dried powder and platinum electrode were placed in a 0.1 mol / L Na2SO4 solution, and a voltage of 1.8 V was applied for activation for 1.5 hours. Then, graphene was added at a mass ratio of 1:0.08, and electrochemical deposition was continued for 1 hour to complete the recombination process.

[0065] (5) Low-temperature calcination and post-treatment: The composite material was placed in a muffle furnace, heated to 400°C at a heating rate of 2°C / min, maintained for 5 hours, and naturally cooled to room temperature. After being taken out, it was washed with deionized water until the pH of the washing liquid was close to neutral, and dried at 60°C for 12 hours to obtain a high-entropy composite oxygen carrier, which was recorded as FeCoNiCuMn-400°C.

[0066] The high entropy composite oxygen carrier prepared in the above steps has been tested to have a specific surface area of ​​55m 2 / g, the pore size distribution is between 2-50nm, the crystal structure is cubic, the oxygen transmission rate is increased by 45%, the sintering resistance is enhanced by more than 35%, and the redox cycle stability exceeds 100 times.

[0067] Using pine wood powder as raw material, chemical chain gasification hydrogen production test was carried out at 800°C, the reduction time was 35min, the synthesis gas yield was 0.96Nm3 / h, the synthesis gas selectivity was 78%, the hydrogen production purity was 99.4%, and after 100 cycles, the performance decayed by 3.5%, showing good reaction characteristics.

[0068] Example 4 Preparation of high entropy composite oxygen carrier FeCoNiCuMn-350℃

[0069] (1) Preparation and mixing of metal salt solution: Metal nitrates were weighed at a molar ratio of Fe:Co:Ni:Cu:Mn=1:1:1:1:1 and dissolved in deionized water to prepare a mixed solution with a concentration of 0.1 mol / L.

[0070] (2) Adding electrolytes and gelling agents: Add 0.05 mol / L NaCl solution and 0.5% PVP solution by mass to the above solution and stir for 30 minutes to form a uniform sol.

[0071] (3) Low-temperature freeze drying: The sol was precooled to -10 °C and then freeze-dried at -40 °C and 0.05 mbar for 24 h to obtain anhydrous gel powder.

[0072] (4) Electrochemical activation and recombination: The freeze-dried powder and platinum electrode were placed in a 0.1 mol / L Na2SO4 solution, and a voltage of 1.5 V was applied for activation for 2 hours. Then, graphene was added at a mass ratio of 1:0.06, and electrochemical deposition was continued for 1 hour to complete the recombination process.

[0073] (5) Low-temperature calcination and post-treatment: The composite material was placed in a muffle furnace, heated to 350°C at a heating rate of 2°C / min, maintained for 6 hours, and naturally cooled to room temperature. After being taken out, it was washed with deionized water until the pH of the washing liquid was close to neutral, and dried at 60°C for 12 hours to obtain a high-entropy composite oxygen carrier, which was recorded as FeCoNiCuMn-350°C.

[0074] The high entropy composite oxygen carrier prepared in the above steps has been tested to have a specific surface area of ​​52 m 2 / g, the pore size distribution is between 2-40nm, the crystal structure is cubic, the oxygen transmission rate is increased by 42%, the sintering resistance is enhanced by more than 32%, and the redox cycle stability exceeds 100 times.

[0075] Using pine wood powder as raw material, chemical chain gasification hydrogen production test was carried out at 800°C, the reduction time was 35min, the synthesis gas yield was 0.95Nm3 / h, the synthesis gas selectivity was 74%, the hydrogen production purity was 99.5%, and after 100 cycles, the performance decayed by 3.6%, showing good reaction characteristics.

[0076] Example 5 Preparation of high entropy composite oxygen carrier FeCoNiCuMn-500℃-high graphene content

[0077] (1) Preparation and mixing of metal salt solution: Metal nitrates were weighed at a molar ratio of Fe:Co:Ni:Cu:Mn=1:1:1:1:1 and dissolved in deionized water to prepare a mixed solution with a concentration of 0.1 mol / L.

[0078] (2) Adding electrolytes and gelling agents: Add 0.05 mol / L NaCl solution and 1.2% PVP solution by mass to the above solution and stir for 30 minutes to form a uniform sol.

[0079] (3) Low-temperature freeze drying: The sol was precooled to -20 °C and then freeze-dried at -50 °C and 0.1 mbar for 24 h to obtain anhydrous gel powder.

[0080] (4) Electrochemical activation and recombination: The freeze-dried powder and platinum electrode were placed in a 0.1 mol / L Na2SO4 solution, and a voltage of 1.0 V was applied for activation for 3 hours. Then, graphene was added at a mass ratio of 1:0.09, and electrochemical deposition was continued for 1 hour to complete the recombination process.

[0081] (5) Low-temperature calcination and post-treatment: The composite material was placed in a muffle furnace, heated to 500°C at a heating rate of 2°C / min, maintained for 4 hours, and naturally cooled to room temperature. After being taken out, it was washed with deionized water until the pH of the washing liquid was close to neutral, and dried at 60°C for 12 hours to obtain a high-entropy composite oxygen carrier recorded as FeCoNiCuMn-500°C-high graphene content.

[0082] The high entropy composite oxygen carrier prepared in the above steps has been tested to have a specific surface area of ​​62 m 2 / g, the pore size distribution is between 2-50nm, the crystal structure is cubic, the oxygen transmission rate is increased by 52%, the sintering resistance is enhanced by more than 42%, and the redox cycle stability exceeds 100 times.

[0083] Using pine wood powder as raw material, chemical chain gasification hydrogen production test was carried out at 800°C, the reduction time was 35min, the synthesis gas yield was 0.98Nm3 / h, the synthesis gas selectivity was 80%, the hydrogen production purity was 99.6%, and after 100 cycles, the performance decayed by 3.2%, showing good reaction characteristics.

[0084] Example 6 Preparation of high entropy composite oxygen carrier FeCoNiCuMn-400°C-high graphene content

[0085] (1) Preparation and mixing of metal salt solution: Metal nitrates were weighed at a molar ratio of Fe:Co:Ni:Cu:Mn=1:1:1:1:1 and dissolved in deionized water to prepare a mixed solution with a concentration of 0.1 mol / L.

[0086] (2) Adding electrolytes and gelling agents: Add 0.05 mol / L NaCl solution and 1.8% PVP solution by mass to the above solution and stir for 30 minutes to form a uniform sol.

[0087] (3) Low-temperature freeze drying: The sol was precooled to -20 °C and then freeze-dried at -50 °C and 0.1 mbar for 24 h to obtain anhydrous gel powder.

[0088] (4) Electrochemical activation and recombination: The freeze-dried powder and platinum electrode were placed in a 0.1 mol / L Na2SO4 solution, and a voltage of 2.0 V was applied for activation for 1 hour. Then, graphene was added at a mass ratio of 1:0.1, and electrochemical deposition was continued for 1 hour to complete the recombination process.

[0089] (5) Low-temperature calcination and post-treatment: The composite material was placed in a muffle furnace, heated to 400°C at a heating rate of 2°C / min, maintained for 4 hours, and naturally cooled to room temperature. After being taken out, it was washed with deionized water until the pH of the washing solution was close to neutral, and dried at 60°C for 12 hours to obtain a high-entropy composite oxygen carrier recorded as FeCoNiCuMn-400°C-high graphene content.

[0090] The high entropy composite oxygen carrier prepared in the above steps has been tested to have a specific surface area of ​​56 m 2 / g, the pore size distribution is between 2-50nm, the crystal structure is cubic, the oxygen transmission rate is increased by 46%, the sintering resistance is enhanced by more than 36%, and the redox cycle stability exceeds 100 times.

[0091] Using pine wood powder as raw material, chemical chain gasification hydrogen production test was carried out at 800°C, the reduction time was 35min, the synthesis gas yield was 0.97Nm3 / h, the synthesis gas selectivity was 81%, the hydrogen production purity was 99.3%, and after 100 cycles, the performance decayed by 3.5%, showing good reaction characteristics.

[0092] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

[0093] The oxygen carrier preparation parameters of the above embodiment are shown in Table 1:

[0094] Table 1

[0095]

[0096] The test results of the high entropy composite oxygen carrier prepared in the chemical chain gasification are shown in Table 2

[0097] Table 2

[0098]

Claims

1. A method for preparing a high entropy composite oxygen carrier, characterized in that: The following steps are involved: S1. Preparation and mixing of metal salt solution: Dissolve nitrates of iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), and manganese (Mn) in deionized water to prepare a metal salt mixed solution with a concentration of 0.1 mol / L. S2. Adding electrolytes and gelling agents: Adding sodium chloride (NaCl) and polyvinylpyrrolidone (PVP) to the above solution, adjusting the ionic strength and viscosity of the solution, and forming a uniform sol. S3. Low temperature freeze drying: precool the sol to -20°C and then freeze at -50°C. The mixture was freeze-dried at 0.1 mbar for 24 hours to obtain anhydrous gel powder. S4. Electrochemical activation and recombination: The freeze-dried powder was placed together with a platinum electrode in a 0.1 mol / L sodium sulfate solution, a voltage of 1.5 V was applied, and electrochemical activation was performed for 2 hours; then graphene was added at a mass ratio of 1:0.05, and electrochemical deposition was continued for 1 hour to complete the recombination process. S5. Low-temperature calcination and post-treatment: The composite material was placed in a muffle furnace, heated to 500°C at a heating rate of 2°C / min, maintained for 4 hours, and then naturally cooled to room temperature; after taking out, it was washed with deionized water and dried for 12 hours to obtain a high-entropy composite oxygen carrier.

2. The method according to claim 1, wherein: The metal salts are weighed in a molar ratio of Fe:Co:Ni:Cu:Mn=1:1:1:1:

1.

3. The method according to claim 1, wherein: The concentration of the sodium chloride is 0.05 mol / L.

4. The method according to claim 1, wherein: The mass fraction of the PVP is 0.5%-2%.

5. The method according to claim 1, wherein: The precooling temperature is -10 to -30°C, the freeze-drying temperature is -40 to -60°C, the freeze-drying pressure is 0.05 mbar to 0.1 mbar, and the freeze-drying time is 24 hours.

6. The method according to claim 1, wherein: The voltage of the electrochemical activation is 1V-3V, the activation time is 1h-3h, and the scanning rate is 5mV / s.

7. The method according to claim 1, wherein: The mass ratio of the graphene to the oxygen carrier is 1:0.05-0.

1.

8. The method according to claim 1, wherein: The temperature of the low-temperature calcination is 300° C.-400° C., the heating rate is 1-4° C. / min, and the holding time is 3h-6h.

9. The method according to claim 1, wherein: The low temperature calcination process can be carried out in air, nitrogen or hydrogen atmosphere.

10. The method according to claim 1, wherein after the low-temperature calcination, the composite material is washed in deionized water until the pH value of the washing liquid is close to neutral; then, it is dried at 60°C for 12 hours until constant weight is reached to obtain a high entropy composite oxygen carrier.

11. The method according to claim 1, wherein: The high entropy composite oxygen carrier has a specific surface area greater than 50m 2 / g, the pore size distribution is between 2nm and 50nm, the crystal structure is cubic, and the redox cycle stability is more than 100 times.

Citation Information

Patent Citations

  • Method for electrochemically preparing graphene

    CN116789125A

  • High-stability transition metal high-entropy oxygen carrier and preparation method and application thereof

    CN117019168A

  • Activation of Waste Metal Oxide as an Oxygen Carrier for Chemical Looping Combustion Applications

    US20150343416A1

  • Composition and method for catalytic reduction of carbon dioxide or carbohydrate

    US20230054550A1

  • Supported ultrafine alloy nanoparticle and preparation method therefor and application thereof

    WO2021017966A1